Design of a Two-Way Conveyor Belt Control System Based on PLC and HMI - Rafi Taufiq Hidayat, Muhammad; Tri Putra Yanto, Doni (Journal of Industrial Automation and Electrical Engineering, 2024)
This research aims to control and monitor the direction of rotation and speed of the conveyor belt based on PLC and HMI. Conveyor belt control settings are carried out using a Toshiba VF-S15 Variable Speed Drive which is controlled by the Simatic S7 1200 1215C Programmable Logic Controller. This induction motor control and monitoring system is implemented on a 0.37 kW induction motor as a conveyor belt drive using the Simatic KTP700 Comfort Human Machine Interface. The test results show that the control and monitoring system for the direction of rotation and speed of the conveyor belt has worked well in automatic mode and manual mode. The HMI display used as an interface for controlling and monitoring the conveyor belt has successfully controlled the conveyor belt and displays conveyor belt speed data close to the same as the speed data obtained from the measuring instrument